MODERN GERMAN ACOUNTANCY. - Schranz, Andrew (The Accounting Review, 1930)
Abstract Before looking at accountancy in Germany, it will be advisable to consider bookkeeping briefly. The foundation of the bookkeeping employed in Germany is the system of double entry derived from the Italian, Lucas Pacioli. In addition to the "Italian Bookkeeping" a more widely used system is the "German Bookkeeping." This system is striking on account of its arrangement for dealing with a great number of bookkeeping items and the possibility it affords for the greater distribution of labor. The French System is a further development of the German system. Here the distribution of labor is carried to such an extent that for every more important account they open a separate book. The recording organization of business enterprises in Germany has made great progress especially in recent decades. With the improvement in the qualifications of the bookkeepers, the enlargement of the business enterprises and the multiplicity of their activities, it was necessary also to improve the accountancy of the enterprise.